Accurate computational approach for singularly perturbed Burger-Huxley equations - Bullo, Tesfaye Aga; Kabeto, Masho Jima; Debela, Habtamu Garoma; Kusi, Gemadi Roba; Robi, Sisay Dibaba (Zielona Góra: Uniwersytet Zielonogórski)
The main purpose of this work is to present an accurate computational approach for solving the singularly perturbed Burger-Huxley equations. The quasilinearization technique linearizes the nonlinear term of the differential equation. The finite difference approximation is formulated to approximate the derivatives in the differential equations and then accelerate its rate of convergence to improve the accuracy of the solution. Numerical experiments were conducted to sustain the theoretical results and to show that the presented method produces a more correct solution than some surviving methods in the literature.
Keywords: singularly perturbed; nonlinear term; Burger-Huxley equations; accurate solution